CHARACTERISTICS OF DISTURBANCES IN NEUROPHYSIOLOGICAL AND PSYCHO-EMOTIONAL STATUS OF PATIENTS WITH VIBRATION DISEASE IN THE POSTEXPOSURE PERIOD - D. V. Rusanova; M. V. Kuleshova; E. V. Katamanova; O. L. Lakhman; V. A. Pankov (Acta Biomedica Scientifica, 2016)
The article presents the results of the studies of the central and peripheral nervous systems, psychoemotional status of patients with vibration disease associated with exposure to the local vibration in the post-exposure period. The studies were performed in patients with vibration disease (n = 18) who do not work in the contact with the local vibration at present. The mean age of the patients was 50.7 ± 5.4 years, the mean length of service in the contact with local vibration -17.9 ± 2.8 years, the mean post-exposure period - 5.2 ± 2.2 years. 30 male persons having no contact with industrial hazard were comprised the control group. Electroencephalography, electroneuromyography, recording of somatosensory evoked potentials were carried out and patients' personality peculiarities were studied. The changes of the brain bioelectrical activity, disorders of the autonomic and afferent regulation of the cerebral level, dysfunction in diencephalic structures, disorders of the subcortical and cortical structures of the central afferent pathways; demyelization of the peripheral nerves of the upper and lower extremities were set in patients with vibration disease in the post-exposure period. Psychological studies have shown that patients with vibration disease in the post-exposure period preserve such psychological peculiarities as neuroticism manifested with inner tension, nervousness and chronic feeling of discomfort; depressive tendencies being a sign of the existing distress, and anxious-hypochondriac features in the structure of personality traits. All of the above result in formation of stable uncompensated clinical conditions observed in patients with vibration disease caused by local vibration exposure, even after the termination of harmful production factors.